Melatih Kreativitas Diri Siswa Dasar Melalui Fun Book Dalam Pembelajaran Ma-tematika Dan Bahasa - Anim, Anim; aryni, Yen; permatasari, Putri lidiana (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
This article discusses the use of Fun Books as a measuring tool to increase students' creativity at elementary school level in mathematics and language learning. This service is carried out with a focus on measuring students' creativity levels before and after implementing the Fun Book as well as evaluating how to stimulate students' creativity in both subjects. The target of the training is selected students, namely SD Negeri No. 010246 Banjar. The students selected were 16 Grade 2 students. The problem seen at this school is that students are still passive in learning, students are not yet creative and have difficulty answering questions asked by the teacher during each lesson in class, there are even 50% of students who are sleepy when taking part in class lessons. The impact of this training was that 13 students were able to use Fun Book media. Evaluation is carried out at the end of the training by distributing questionnaires to measure the participant's level of understanding. The questionnaire contains questions related to the respondent's identity; general questions related to mathematics and language learning and specific questions related to Fun Book media. The calculation of the questionnaire used the Guttman scale. The evaluation results showed that 89.84% had increased knowledge seen from the calculation of the questionnaire per individual and per question asked and the participation and enthusiasm of students during activities using the Fun Book.Keywords: Fun Book; creativity; student